2011
DOI: 10.1103/physreva.84.062505
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of transitions in internal rotor molecules to a possible variation of the proton-to-electron mass ratio

Abstract: Recently, methanol was identified as a sensitive target system to probe variations of the proton-to-electron mass ratio μ [Jansen et al., Phys. Rev. Lett. 106, 100801 (2011)]. The high sensitivity of methanol originates from the interplay between overall rotation and hindered internal rotation of the molecule; that is, transitions that convert internal rotation energy into overall rotation energy, or vice versa, have an enhanced sensitivity coefficient, K μ . As internal rotation is a common phenomenon in poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 42 publications
2
34
0
Order By: Relevance
“…It was shown by Jansen et al 37,93 that a pure torsional transition in methanol has a sensitivity coefficient of K μ = −2.5. However, pure torsional transitions are forbidden, since they possess a different torsional symmetry.…”
Section: Internal Rotation: From Methanol To Methylaminementioning
confidence: 99%
See 3 more Smart Citations
“…It was shown by Jansen et al 37,93 that a pure torsional transition in methanol has a sensitivity coefficient of K μ = −2.5. However, pure torsional transitions are forbidden, since they possess a different torsional symmetry.…”
Section: Internal Rotation: From Methanol To Methylaminementioning
confidence: 99%
“…Higher order parameters pose a problem since their physical interpretation is not always clear. Jansen et al 37,93 derived the scaling relations for these higher-order constants by considering them as effective products of lower-order torsional and rotational operators. Ilyushin et al 94 showed that the scaling of the higher order constants only contributes marginally to the sensitivity coefficient of a transition.…”
Section: Internal Rotation: From Methanol To Methylaminementioning
confidence: 99%
See 2 more Smart Citations
“…Kozlov et al [1] showed that transitions that convert rotational motion into inversion motion, and vice versa, in the different isotopologues of hydronium (H 3 O + ) have K μ coefficients ranging from −219 to +11 [2]. Similarly, Jansen et al [3,4] and Levshakov et al [5] showed that transitions that convert internal rotation into overall rotation in the different isotopologues of methanol have K μ coefficients ranging from −88 to +330. Here, the sensitivity coefficient K μ is defined by…”
Section: Introductionmentioning
confidence: 99%